ӘЛЕУМЕТТІК-КӘСІПКЕРЛІК КОРПОРАЦИЯЛАРДЫҢ ДАМУЫ - ӨҢІРЛІК ЭКОНОМИКАДАҒЫ ЖАҢА ВЕКТОР - M. Zh. Kuttybai (Экономика: стратегия и практика)
The article considers the peculiarities of creation and functioning in Kazakhstan of specialized institutions of public-private partnership - social-entrepreneurial corporations. Based on the study of foreign experience in creating similar organizations, the advantages and problems of their functioning are determined. The Kazakhstan model of a socio-entrepreneurial corporation is created as a corporation of a non-commercial type, but it is designed to solve the problems of extracting profits and investing in the social and economic development of the regions. Based on the generalization of the world experience in the development of regional development institutions, it is determined that the socio-entrepreneurial corporations of Kazakhstan are created in the final form of business partnerships, characteristic of developed countries. This feature on the one hand allows our socially-entrepreneurial corporations to use advanced mechanisms, but on the other hand, a sharp non-evolutionary transition to the final stage is a definite limiter of their operational functionality.